Peran Literasi Keuangan Bagi Ibu Rumah Tangga Dalam Meningkatkan Kesejahteraan Keluarga - Pratiwi, I Gusti Ayu Made Agung Mas Andriani; Suarbawa, I Wayan; Kusmawan, I Made Hary (Universitas Tabanan, 2025)
Abstract tells the basic content of writing clearly and briefly, so it can be used as guidance for the readers in determining the level of relevance towards their need in a short time. Abstract should be informative and give clear statement about the problem, approach or suggested solution, and the result that shows the solution of the problem. The abstract should 90 until 200 words longer. Abstract should be written in past tense and use nomenclature standard. It is suggested to use keywords that shows the knowledge field related to the research.